Guidelines for Developing Academic Administration in Schools under The Secondary Educational Service Area Office Buriram - Powat, Pongpon; Duangchatom, Kritkanok (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Academic administration is considered important in schools. Because academic administration in schools is all kinds of activities, Improving teaching for students to achieve the most effective results. Therefore, this research aims to 1) study the current, desirable state and priority need index of academic administration of schools under the secondary educational service area office Buriram. 2) study the guidelines development of academic administration of schools under the secondary educational service area office Buriram. Methodology: The research process was divided into 2 phases: Phase 1; to study the current state, desirable state, and need analysis for academic administration in schools. The sample group used in the research was administrators and teachers, 311 people. The research tool was a questionnaire, confidence of the whole .77. The statistics used for data analysis were mean, percentage, and standard deviation. Phase 2; to study guidelines for developing academic administration in schools. The target group is 5 experts. The research tool was interview form and data analysis by content analysis. Results: 1. The current state overall was low level, and the desirable state overall was at a high level. The need assessment for academic administration in schools ranked from high to low level was 1) development of Instructional 2) educational supervision 3) measurement and evaluation 4) curriculum development 5) development of Innovative media technology of education 6) internal quality assurance and educational standard. 2. Guidelines for the academic administration of the school Under secondary educational service area office Buriram, consists of 15 guidelines, including curriculum administration with 3 guidelines, learning process development with 3 guidelines, educational supervision with 1 guidelines, measurement and evaluation with 3 guidelines, internal quality assurance and educational standards with 2 guidelines, and development of educational media, innovation, and technology 3 guidelines. Conclusion: The school academic administration that has the greatest need is the development of the learning process. The guidelines section consists of 15 guidelines as follows: Development of Instructional, guidelines are 1) child Center Learning 2) learning for the development of learners’ potential and excellence 3) development in learning management for teachers. Educational supervision, guidelines are participation in educational supervision Measurement and evaluation, guidelines are 1)creation and development of tools for measurement and evaluation 2) participation for measurement and evaluation 3) regulation Guidelines and patterns of measurement and evaluation. Curriculum development, guidelines are 1) the school curriculum created 2) the goal, and vision of the school curriculum 3) the analysis of the core curriculum Development of innovative media technology in education, guidelines are 1) analysis of necessary for the use of innovative media technology of education 2) support for media Innovation and learning management technology Internal quality assurance and educational standards, guidelines are 1) analyze vision and goals of internal quality assurance and educational standards planning 2) creation and development of assessment and measurement tools for internal quality assurance and educational standards.